The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/2013wr014055
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic collocation method for strongly nonlinear problems: 1. Transform by location

Abstract: [1] In this work, we propose a new collocation method for uncertainty quantification in strongly nonlinear problems. Based on polynomial construction, the traditional probabilistic collocation method (PCM) approximates the model output response, which is a function of the random input parameter, from the Eulerian point of view in specific locations. In some cases, especially when the advection dominates, the model response has a strongly nonlinear profile with a discontinuous shock or large gradient. This nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…For example, it has been demonstrated that the mean and variance of hydraulic head obtained with only the first few leading KL expansion terms (e.g., = 6 for a 1D case) is very close to those obtained from thousands of Monte Carlo simulation with full models [25]. Similar observations are also reported in Li et al [26] and Liao and Zhang [27]. In a quantitative sense, if the polynomial chaos expansion (PCE) is used to construct a surrogate model for the state variables (e.g., hydraulic head) and KL expansion on the model parameter (e.g., log hydraulic conductivity), the number of model evaluation required to obtain the PCE coefficients is ( + )!/ !/ !, where is the degree of PCE.…”
Section: Gaussian Variablessupporting
confidence: 83%
See 1 more Smart Citation
“…For example, it has been demonstrated that the mean and variance of hydraulic head obtained with only the first few leading KL expansion terms (e.g., = 6 for a 1D case) is very close to those obtained from thousands of Monte Carlo simulation with full models [25]. Similar observations are also reported in Li et al [26] and Liao and Zhang [27]. In a quantitative sense, if the polynomial chaos expansion (PCE) is used to construct a surrogate model for the state variables (e.g., hydraulic head) and KL expansion on the model parameter (e.g., log hydraulic conductivity), the number of model evaluation required to obtain the PCE coefficients is ( + )!/ !/ !, where is the degree of PCE.…”
Section: Gaussian Variablessupporting
confidence: 83%
“…The advantage of the proposed method is that KL expansion has the capability to conduct the model dimensionality reduction. If it is further incorporated with polynomial chaos expansion on the state variables, such as hydraulic head in the single-phase flow problem [25], saturation in the multiphase problem [26], and contaminant transport problem [27], the computational cost to perform uncertainty analysis in the hydrological research can be greatly reduced. The proposed KL-based multiscale random fractal field generator provides the foundation to establish a high-efficiency stochastic analysis framework.…”
Section: Introductionmentioning
confidence: 99%
“…The Karhunen-Loeve expansion method can convert a correlated random function into a polynomial with independent and identically distributed Gaussian random variables [45,46]. Since the log hydraulic conductivity, Y, is heterogeneous and spatial correlated.…”
Section: Unconditional and Conditional Karhunen-loeve Expansion Methodsmentioning
confidence: 99%
“…To obtain the coefficients, the probabilistic collocation method can be used, which is derived on the basis of weighted residual method. Denoting as the differential operator in Equation (1), the stochastic partial differential equation of groundwater flow model can be written as [44,46]:…”
Section: Probabilistic Collocation Methodsmentioning
confidence: 99%
See 1 more Smart Citation